Effects of interferon, ribavirin, and iminosugar derivatives on cells persistently infected with noncytopathic bovine viral diarrhea virus. - Durantel, D; Carrouée-Durantel, S; Branza-Nichita, N; Dwek, R; Zitzmann, N (American Society for Microbiology, 2004)
Persistent infection with hepatitis C virus (HCV) is a major cause of chronic hepatitis in humans. In chronic carriers, the viral infection induces liver damage that predisposes the patient for cirrhosis and can lead to hepatocellular carcinoma. Current chemotherapies are limited to alpha interferon (IFN-alpha) used either alone or in combination with ribavirin (RBV). In addition to its limited efficacy, this treatment is frequently poorly tolerated because of its side effects. The urgently needed development of new drugs is made difficult by the lack of an in vitro or in vivo infectivity model, and no cell line has been found so far to reliably and reproducibly support HCV infection. For this reason, the closely related pestivirus bovine viral diarrhea virus (BVDV) has sometimes been used as a surrogate in vitro infectivity model. In this study we used an MDBK cell line persistently infected with noncytopathic BVDV to assess the antiviral effect of IFN-alpha and RBV, the two drugs currently in clinical use against HCV. The same system was then used to evaluate the potential of two classes of iminosugar derivates to clear noncytopathic BVDV infection from MDBK cells. We show that treatment with long-alkyl-chain deoxynojirimycin derivatives, which are inhibitors of the endoplasmic reticulum (ER)-resident alpha-glucosidases, can greatly reduce the amount of secreted enveloped viral RNA. Long-alkyl-chain deoxygalactonojirimycin derivatives, which do not inhibit ER alpha-glucosidases, were less potent but still more effective in this system than IFN-alpha or ribavirin.